The role of calcineurin in the lung fibroblasts proliferation and collagen synthesis induced by basic fibroblast growth factor - 陈亚红 赵鸣武 符民桂 姚婉贞 唐朝枢 (Chinese medical journal, 2003)
Objective To investigate the role of calcineurin (CAN) in the lung fibroblast proliferation and collagen synthesis induced by basic fibroblast growth factor (bFGF).Methods We used Western blot and immunohistochemical methods for investigating the content and distribution of calcineurin in the lung tissue. Calcineurin activity in different tissues was measured using ^32P-labelled substrate. In the primary culture of lung fibroblasts, ^3H-thymidine (^3H-TdR) and ^3H-proline incorporation methods were used to study the effect of cyclosporin A (CsA), an inhibitor of calcineurin, on the lung fibroblast DNA and collagen synthesis stimulated by bFGF.Results We found that calcineurin was expressed in lung tissue and has phosphatase activity (7.1±2. 0 pmol Pi/mg pr/min). CsA (10^8 -10^6 mol/L) inhibited lung fibroblast ^3H-TdR incorporation induced by bFGF in a dose-dependent manner, with the inhibitory rates by 20%, 46% and 66% ( P <0. 01 ). CsA (10^7 -10^6mol/L) inhibited ^3H-proline incorporation in lung fibroblasts stimulated bybFGF, with the inhibitory rates by 21% and 37% ( P <0. 01 ). In a culture medium, CsA ( 10^8 - 10^6mol/L) inhibited ^3H-proline secretion induced by bFGF in a dose-dependent manner, with the inhibitory rates by 19%, 29% (P <0. 05) and 56% (P <0. 01 ). CsA (10^-7mol/L) could inhibit calcineurin activity by 44% in lung fibroblasts ( P<0.01 ).Conclusions Calcineurin is expressed in lung tissue and has phosphatase activity. It is involved in the bFGF stimulated lung fibroblast DNA and collagen synthesis.